EFFECT OF FEEDING LIV-52 POWDER ON GROWTH PERFORMANCE OF BROILER CHICKS - Suryawanshi, V P; Bahiram, K B; Ramteke, B N; Nipane , S F; Narkhede, H P (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
An experiment was conducted on 60 broiler chicks from day old to six weeks of age to study the effect of feeding Liv-52 powder on their performance. The birds were divided into three groups consisting 20 in each. T1 (control) fed on standard broiler diet, T2 and T3 groups were supplemented Liv-52 with 0.05 and 0.1% of feed. All the experimental groups were isocaloric. The average final live body weight at six weeks of age and weekly gain in body weight were significantly higher in T2 and T3 group supplemented with Liv-52 than control. The average feed consumption from 0-6 weeks of age was 3292.5, 3496.78 and 3503.05 gms in T1 (control), T2 and T3 groups respectively and the corresponding feed efficiency at 6th week of age was 2.06, 1.62 and 1.73 . It was revealed that feed efficiency was more in Liv-52 treated group as compared to control group.